2013
DOI: 10.1103/physrevd.87.034507
|View full text |Cite
|
Sign up to set email alerts
|

Towards the phase diagram of dense two-color matter

Abstract: We study two-color QCD with two flavors of Wilson fermion as a function of quark chemical potential µ and temperature T . We find evidence of a superfluid phase at intermediate µ and low T where the quark number density and diquark condensate are both very well described by a Fermi sphere of nearly-free quarks disrupted by a BCS condensate. Our results suggest that the quark contribution to the energy density is negative (and balanced by a positive gauge contribution), although this result is highly sensitive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
144
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(189 citation statements)
references
References 33 publications
35
144
3
Order By: Relevance
“…It is interesting to note, that this fit gives a satisfactory description of the data up to µ ∼ 1055 MeV (µa ∼ 0.6). Thus, one sees that the chiral condensate drops slower with increasing chemical potential than ChPT predicts (similar slower decrease of the form qq ∼ 1/µ was observed in [21] with N f = 2 Wilson quarks). Figure 3.…”
Section: The Chiral Condensatesupporting
confidence: 56%
See 1 more Smart Citation
“…It is interesting to note, that this fit gives a satisfactory description of the data up to µ ∼ 1055 MeV (µa ∼ 0.6). Thus, one sees that the chiral condensate drops slower with increasing chemical potential than ChPT predicts (similar slower decrease of the form qq ∼ 1/µ was observed in [21] with N f = 2 Wilson quarks). Figure 3.…”
Section: The Chiral Condensatesupporting
confidence: 56%
“…The main activity in two-color QCD was later continued by the Swansea group (S. Hands and collaborators) for the two-flavor theory with Wilson fermions [19][20][21][22]. In a low temperature scan of the phase diagram the authors observed a hadronic phase, followed by the BCS phase with deconfinement, but did not encounter the BEC phase.…”
Section: Introductionmentioning
confidence: 99%
“…Especially interesting is to understand the effect of a non-zero baryon density on the breaking/recovery of the chiral symmetry. Similar investigations were performed in [3,5,6] for N f = 2 with Wilson fermions and in [7] [8] with N f = 4 and 8 flavors of staggered fermions respectively. However, Wilson fermions explicitly violate the chiral symmetry [9], thus they may not reveal all the phase transition lines in the QC 2 D phase diagram.…”
Section: Introductionsupporting
confidence: 56%
“…In [13] the gap in the 3 + 1d Nambu Jona-Lasinio model (a relativistic analog of the original BCS model) was shown to be approximately constant above onset, independent of and numerically much smaller than μ, consistent with the BCS result ∼ UV exp(−c 2 UV /μ 2 ). In QCD with gauge group SU(2) there is a so-called quarkyonic regime above onset where ∝ μ 2 [16]; this is consistent with degenerate fermions in 3 + 1d with a gap ∼ O( QCD ) independent of μ. It is also very different from the result /μ ∼ O(10 −7 ) obtained by self-consistent diagrammatic techniques [7], although comparable with the large values of /μ obtained in [5], where it was found that depends sensitively on the treatment of screening effects, and in particular on the reduction of screening once the superfluid gap forms.…”
Section: Discussionmentioning
confidence: 57%
“…In the region of μ studied it is clear that varies strongly with and is of the same order of magnitude as the chemical potential μ, which are notable features of this particular model proposed in [1], and indicative of strong interactions at the Fermi surface. This conclusion holds in both normal and anomalous channels, appears to be independent of volume, and is striking enough to be robust against uncertainties introduced by the ad hoc nature of our analysis [an analytic form against which to fit the dispersion E(k) would be very valuable], the IR and UV artifacts inherent in studies of lattice models with μ = 0 [16], and lack of knowledge of the physical anisotropy a t /a s . On the basis of the three chemical potentials studied both and k F appear to scale superlinearly with μ, in qualitative agreement with (10).…”
Section: Quasiparticle Dispersionmentioning
confidence: 57%